PEMBENTUKAN KARAKTER KEPEMIMPINAN DAN ANTI-BULLYING PADA ANAK USIA SEKOLAH DASAR (Sosialisasi dan Pelatihan bagi Anak-Anak Panti Asuhan Cipta Waris Papua Kabupaten Sorong) - Adolfina Putnarubun; I Dewi Ayu N. U. Sastrani; Chesye Figeline Liklikwatil; Leidy Damima; Daniel Dinelson Asmuruf; Sisilia Euodia Santi; Heru Hiskia Hegemur; Jenifer Palijama; Amelia Rerei; Rendy Kilala (Nusantara Hasana Journal, 2026)
This community service activity aims to increase children's understanding of the dangers of bullying and instill leadership values ​​from an early age. The program was implemented at the Cipta Waris Papua Orphanage in Sorong Regency, using interactive outreach methods through material delivery, discussions, educational games, and question-and-answer sessions. Fourteen elementary school-aged children participated in the activity. Results showed that participants understood the meaning of bullying, its forms, and its negative impacts. Furthermore, this activity also increased children's understanding of the importance of responsibility, cooperation, and self-confidence as part of leadership character. This program is expected to contribute to children's character development and create a social environment of mutual respect.